The Role of Civil Society in the Tunisian Transformation Process - Rothers, Simon (2018)
Abstract: Political transformation scholars identified a new object of research through the course of the so-called "Arab Spring" that began in 2010 - the democratization of Arab countries. However, Tunisia is the only country in which the transformation process resulted in a democratic political system with constitutional rights and free elections, achievements that remain to this day. This paper investigates the importance and role of civil society during the transformation process in Tunisia. Theoretically, this paper integrates a participative framework of civil society with a three-stage-model of democratic transformation, inspired by French philosopher Montesquieu. In the descriptive empirical section, events are summarized that took place between 2000 and 2017. In the subsequent sections, the paper frames events from this period in a historical and sociological context: from the Ottomans until the authoritarian ruler Ben Ali, thereby drawing special attention to the unique evolution o